Fluoride release and fluoride-recharging ability of three different sealants - Patil, Sneha; Kontham, Ujwal R.; Kontham, Rakesh K.; Patil, Smita S.; Kamble, Sanjay P. (Journal of Indian Society of Pedodontics and Preventive Dentistry, 2020)
Background: We aimed to determine the fluoride release and fluoride-recharging ability of a sealant containing surface pre-reacted glass (S-PRG) ionomer filler particles (BeautiSealant) with a fluoride-releasing resin sealant (Helioseal F), and a glass-ionomer sealant (Fuji VII). Materials: And: Methodology: Forty-eight disc-shaped specimens of each material were immersed in deionized water to determine the fluoride release utilizing a fluoride ion-selective electrode. After 21 days, 8 specimens were soaked in 0.22% Sodium Fluoride solution for 2 min; 8 specimens were coated with 1.23% Acidulated Phosphate Fluoride (APF) gel for 4 min, and the fluoride-recharging ability was evaluated for 40 days. Data were analyzed using one way-ANOVA and Bonferroni post hoc tests. Results: Total fluoride release over the 21-day period was: Fuji VII > BeautiSealant > Helioseal F, (P = 0.000). After refluoridation of the specimens with 0.22% Sodium Fluoride solution, the cumulative fluoride release during the 40-day period for each material was: BeautiSealant > Fuji VII > Helioseal (P = 0.000). After exposure to 1.23% APF gel, the cumulative fluoride release during the 40-day period for each material was: BeautiSealant > Fuji VII > Helioseal F (P = 0.000). Conclusion: Glass ionomer-based sealants (Fuji VII) exhibited higher initial fluoride release whilst the surface pre-reacted glass-ionomer filler containing sealant (BeautiSealant) demonstrated superior fluoride recharging properties.

Aldol Condensation of Furfural with Acetone by Using Mg-Al-O-t-Bu HT Catalyst and Kinetic Studies - Patil, Sneha; Kamble, Paresh; Vinod, Chathakudath Prabhakaran; Rathod, Virendra; Kantam, Mannepalli Lakshmi (Industrial & Engineering Chemistry Research, 2025)
An environment-friendly method for producing jet fuel precursors involves the aldol condensation of biomass-derived chemicals. In this study, the condensation reaction between furfural and acetone was performed using a Mg-Al-O-t-Bu hydrotalcite (HT) catalyst, achieving a furfural conversion of 99% and a selectivity of 82% toward 4-(2-furyl)-3-buten-2-one (FAc). The kinetics of the process were evaluated using a Langmuir-Hinshelwood-Hougen-Watson (LHHW) model across a range of temperatures, and the model showed an excellent fit to the experimental data. The effect of different catalysts, reaction temperatures, catalyst loadings, molar ratios, and reaction times was systematically investigated. The Mg-Al-O-t-Bu HT catalyst was extensively analyzed through techniques such as XRD, XPS, FTIR, nitrogen adsorption-desorption measurements, and CO2-TPD. The catalyst exhibited excellent stability, maintaining its performance consistently across five successive reaction cycles with no notable decline in activity. These findings highlight the industrial relevance of Mg-Al-O-t-Bu HT as a robust and recyclable solid base catalyst for biomass upgrading, with strong potential for process scale-up in renewable fuel production.